Community Involvement Based on Community-Based Tourism Principles in the Development of Area-Based Tourism in Cirebon Regency - Slamet Usman Ismanto; Dian Indira; Meilanny Budiarti Santoso (Jurnal Manajemen Pelayanan Publik, 2023)
Tourism has a complex activity that includes many aspects, such as social, political, cultural, religious, and economic aspects. Tourism activities also cannot be separated from the existence of local communities as owners of culture, so tourism development efforts must pay attention to the participation of local communities around the Tourism Attraction. This study aims to describe the involvement of residents in the Talun Area of Cirebon Regency in the development of the tourism sector which has experienced a strengthening of commitment and an increase in the intensity of developing the tourism sector since before the Covid-19 pandemic. A descriptive method with a qualitative approach is used in this study. Data collection techniques were carried out through in-depth interviews, literature studies, and documentation studies. Data validation test was carried out by source triangulation. The results of the study show that: First, in the process of developing the area-based tourism sector in Talun, the source of the initiative still comes from the government, in this case, the the District Head (District Head (Camat)). Second, the characteristics of the Talun community, which are open, are more receptive to the idea of area-based tourism development. Third, community involvement in regional-based tourism development requires three prerequisites, namely leadership in administrative areas that become tourist areas, the growth of tourism culture, and active communities as supporters and drivers of tourism.